Harinatha Reddy M wrote:

For example:
[ 9, [ 3, 4, [ [ 2 ] ] ] ]   =  0

In this case we need to fnid the sum of
9, [3,4, [[2]]]

So if we look at it in the equation format
9+ (-(3+4+ -(-(2))))

i.e 9+ (-(3+4+2))
= 9+ (-(9))
= 9-9
 = 0

echo "[ 1, [ 2 ], [ 3 ] ]" | perl -ne'
  chomp;
  print;
  1 while s/\[([^\]]*)\]/-($1)/;
  s/,/+/g;
  print " = ", -eval, $/;
'
[ 1, [ 2 ], [ 3 ] ] = -4


--
Ruud

--
To unsubscribe, e-mail: beginners-unsubscr...@perl.org
For additional commands, e-mail: beginners-h...@perl.org
http://learn.perl.org/


Reply via email to